Detection of tilapia lake virus (TiLV) infection by PCR in farmed and wild Nile tilapia (Oreochromis niloticus) from Lake Victoria. Issue 8 (23rd February 2018) - Mugimba, K K; Chengula, A A; Wamala, S; Mwega, E D; Kasanga, C J; Byarugaba, D K; Mdegela, R H; Tal, S; Bornstein, B; Dishon, A; Mutoloki, S; David, L; et al.
Abstract: Tilapia lake virus disease (TiLVD) has emerged to be an important viral disease of farmed Nile tilapia ( Oreochromis niloticus ) having the potential to impede expansion of aquaculture production. There is a need for rapid diagnostic tools to identify infected fish to limit the spread in individual farms. We report the first detection of TiLV infection by PCR in farmed and wild Nile tilapia from Lake Victoria. There was no difference in prevalence between farmed and wild fish samples ( p  = .65), and of the 442 samples examined from 191 fish, 28 were positive for TiLV by PCR. In terms of tissue distribution, the head kidney (7.69%, N  =   65) and spleen (10.99%, N  =   191), samples had the highest prevalence ( p  < .0028) followed by heart samples (3.45%, N  =   29). Conversely, the prevalence was low in the liver (0.71%, N  =   140) and absent in brain samples (0.0%, N  =   17), which have previously been shown to be target organs during acute infections. Phylogenetic analysis showed homology between our sequences and those from recent outbreaks in Israel and Thailand. Given that these findings were based on nucleic acid detection by PCR, future studies should seek to isolate the virus from fish in Lake Victoria and show its ability to cause disease and virulence in susceptible fish.